Structural and Functional Characterization of PR-4 SUGARWINs From Sugarcaneand Their Role in Plant Defense - Franco, Flávia P.; Dias, Renata O.; Toyama, Danyelle; Henrique-Silva, Flávio; Moura, Daniel S.; Silva-Filho, Marcio C. (Frontiers in Plant Science, 2019)
SUGARWIN1 and 2 are defense proteins from sugarcane. Their gene expression is known to be induced in response to wound and Diatraea saccharalis damage. Although the recombinant SUGARWIN protein does not affect insect development, it promotes significant morphological and physiological changes in Fusarium verticillioides and Colletotrichum falcatum, which lead to fungal cell death via apoptosis. In this study, we deepen our understanding of the role of SUGARWINs in plant defense and the molecular mechanisms by which these proteins affect fungi by elucidating their molecular targets. Our results show that SUGARWINs play an important role in plant defense against opportunistic pathogens. We demonstrated that SUGARWINs are induced by C. falcatum, and the induction of SUGARWINs can vary among sugarcane varieties. The sugarcane variety exhibiting the highest level of SUGARWIN induction exhibited a considerable reduction in C. falcatum infection. Furthermore, SUGARWIN1 exhibited ribonuclease, chitosanase and chitinase activity, whereas SUGARWIN2 exhibited only chitosanase activity. This variable enzymatic specificity seems to be the result of divergent amino acid composition within the substrate-binding site.